Experimental Studies on Work Functions of Li+ Ions and Electrons in the Battery Electrode Material LiCoO2: A Thermodynamic Cycle Combining Ionic and Electronic Structure. Issue 18 (12th March 2018) - Schuld, Stephan; Hausbrand, René; Fingerle, Mathias; Jaegermann, Wolfram; Weitzel, Karl‐Michael
Abstract: The release of Li + from stoichiometric LiCoO2 (LCO) – a typical battery electrode material – is investigated by means of thermionic emission. Analysis of the data leads to an ionic work function of wLi+ (LCO) = 4.1 eV. Combination of this value with the electronic work function we− (LCO) = 5.1 eV, also measured in this work by photoelectron spectroscopy, and with information available from the literature allows the set up, for the first time, of a complete thermodynamic cycle for a Li//LiCoO2 battery. An open circuit cell voltage of 2.4 eV is derived in line with available literature information. The proof‐of‐principle study presented here provides experimental data on the binding energy values, i.e., chemical potentials, of Li + ‐ions and electrons and thus of Li‐atoms in LiCoO2 as a battery cathode and is expected to open access to a better understanding and thus to a better design of battery materials. Abstract : A complete thermodynamic cycle for the battery system Li//LiCoO2 is presented taking into account ionic and electronic work functions.